In vitro Radio Protective Effects of Metformin on Human Lymphocytes Irradiated with Gamma Rays - Salman, Ali Niama; Shafi, Farha A. Ali; Al-Zayadi, Abdual Sahib Kadhim (Iraqi Journal of Science, 2023)
Radio protective effects of metformin and its ability to alter the spontaneous and induced genotoxic and cytotoxic levels effects on human peripheral blood lymphocytes were investigated in this study. Metformin, a hypoglycemic oral drug, is a biguanide derived from Galega officinalis that is widely utilized in controlling type 2 diabetes mellitus. Whole blood samples from 10 healthy donors (5 males and 5 females) were exposed to two doses of gamma-rays (1 and 2 Gray). Lymphocytes in cultures were treated with metformin (10 and 50µM) before gamma-irradiation. Cytokinesis-block micronucleus test was used to evaluate the protective effects of metformin on radiation induced genomic damage, cytostasis and cytotoxicity, via scoring micronuclei and nucleoplasmic bridges in once divided binucleated cells as well as counting nuclear division index. The results of the current study revealed that the increase in micronuclei and nucleoplasmic bridges rate is associated with the decrease of nuclear division index in human lymphocytes exposed to gamma radiation in a dose dependent manner. Metformin effectively decreased the rate of spontaneous micronuclei and nucleoplasmic bridges paralleled with the control as well as increased nuclear division index. Moreover, treatment of whole blood samples with metformin (10 and 50 µM), 2 h preceding to irradiation, remarkably reduced rate of micronuclei and nucleoplasmic bridges accompanied with an increase in nuclear division index rate. The results introduced metformin to be an effective radio protector against DNA damage induced by gamma radiation in human lymphocytes and that it can be used to develop radio protective materials for protection cells of cancer patients from the genomic damage prompted via radiotherapy.